DISCOVERY LEARNING AS AN INSTRUCTIONAL APPROACH TO ENHANCING STUDENTS’ LEARNING OUTCOMES - Cinta Septiana (Teaching and General Education Studies, 2026)
Improving students’ learning outcomes is a persistent challenge in contemporary education, particularly in learning environments that still rely heavily on teacher-centered instructional practices. Such approaches often limit students’ opportunities to actively engage in learning, resulting in superficial understanding and low academic achievement. This scholarly article aims to examine Discovery Learning as an instructional approach that can enhance students’ learning outcomes through active participation, inquiry, and meaningful learning experiences. Using a qualitative, literature-based approach, this article synthesizes relevant theories, models, and empirical findings related to Discovery Learning and its educational implications. The discussion focuses on the theoretical foundations of Discovery Learning, its key characteristics and instructional stages, and its contribution to cognitive, affective, and psychomotor learning outcomes. The analysis indicates that Discovery Learning encourages learners to construct knowledge independently, develop higher-order thinking skills, and increase motivation and engagement. Furthermore, Discovery Learning aligns with constructivist principles and supports long-term knowledge retention. In conclusion, Discovery Learning is a pedagogically sound instructional approach that can significantly improve students’ learning outcomes when implemented with appropriate guidance and instructional design. This article recommends that educators integrate Discovery Learning into classroom practice and encourages further scholarly exploration to strengthen its theoretical and practical application across diverse educational contexts.